Search strategy for sleptons and dark matter using the LHC as a photon collider - Beresford, L; Liu, J (American Physical Society, 2019)
We propose a search strategy using the LHC as a photon collider to open sensitivity to scalar lepton (slepton l˜) production with masses around 15 to 60 GeV above that of neutralino dark matter χ˜01. This region is favored by relic abundance and muon ðg − 2Þμ arguments. However, conventional searches are hindered by the irreducible diboson background. We overcome this obstruction by measuring initial state kinematics and the missing momentum four-vector in proton-tagged ultraperipheral collisions using forward detectors. We demonstrate sensitivity beyond LEP for slepton masses of up to 200 GeV for 15 ≲ Δmðl˜; χ˜ 0 1Þ ≲ 60 GeV with 100 fb−1 of 13 TeV proton collisions. We encourage the LHC collaborations to open this forward frontier for discovering new physics.